Openness and competitiveness of economies of the East European countries and the former Soviet Union - Józef Misala (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
In the contemporary world the development of every country is based not only on the utilization of domestic factors but also, on a larger and larger scale, on external factors. The basic prerequisites for their effective use are the openness of a given economy and its competitiveness. In the present study these problems are discussed, and information on the degree of openness and competitiveness of the East European countries and the former Soviet Union (for short EE countries) is given.
Keywords: 330; Außenwirtschaft; Internationaler Wettbewerb; Osteuropa; GUS-Staaten